Identification of sources of resistance against Aphid, Uroleucon compositae (Theobald) in safflower: IDENTIFICATION OF SOURCES OF RESISTANCE AGAINST APHID IN SAFFLOWER - P S SRINIVAS; PANATHULA CHAITHANYA; A K SAXENA (Journal of Oilseeds Research, 2019)
Safflower (Carthamus tinctorius L.) is one of the most important traditional rabi oilseed crops grown in India. Safflower aphid, Uroleucon compositae (Theobald) is the key pest which causes yield losses to the extent of 30 to 78 per cent if not managed properly. Use of resistant varieties is one of the important components of IPM in safflower as the crop is mainly grown under resources poor conditions. The experiments were conducted during rabi, 2018-2019 at ICRISAT Farm, ICAR- IIOR, Hyderabad to evaluate 50 safflower germplasm accessions and 20 varieties for their reaction to aphids under artificial infestation. Test entries were infested with aphids artificially by transferring infested plants froman infester block raised separately. The reaction was recorded and categorized based on Aphid Infestation Index (AII) on 1.0 to 5.0 scale. Ten germplasm accessions, viz. GMU-671, GMU-599, GMU-3256, GMU-5133, GMU-5848, GMU-7868, GMU-7869, GMU-7870, GMU-7885, GMU-7917 were found moderately resistant to aphids with an average AII ranging from 2.3- 3.0. Out of 21 varieties evaluated, one variety, Girna was found resistant with an average AII of 2.0. Seven varieties viz. SSF-748, Bhima, A-1, SSF-708, PBNS-12, SSF-733 and Manjira were found moderately resistant to aphids with an average AII ranging from 2.3 to 3.0.